Synthesis and characterization of poly (Ethylene Glycol) dimethacrylate-based bionanocomposites with hydroxyapatite from rohu fish (Labeo rohita) bones - Inam, Bushra; Jamila, Nargis; Khan, Naeem; Nishan, Umar; Rauf, Aleesha; Shujah, Shaukat; Shah, Azhar Ul Haq Ali; Ibrahim, Mohamed A.; Kim, Kyong Su (Penerbit Universiti Kebangsaan Malaysia, 2024)
Hydroxyapatite (HA) has gained significant recognition as a bioceramic with widespread utilization in diverse biomedical fields such orthopedics and dentistry. The present study was aimed to isolate hydroxyapatite from rohu fish bones and integrate it into biomaterials with the potential for use in dentistry. Nanocomposite films were developed by combining hydroxyapatite and irgacure with poly (ethylene glycol) dimethacrylate (PEGDMA) and characterized by SEM, DSC, FTIR spectroscopy, and XRD techniques. The SEM study identified HA as nanospheres with crystal sizes below 30 nm. When incorporated into PEGDMA, these nanoparticles aggregated, potentially disrupting polymer chain interactions and affecting the films’ mechanical properties. The XRD pattern obtained from the fish bone subjected to higher temperature calcination exhibited highly intense and sharp peaks, indicating the removal of the organic portion. The FTIR results confirmed the disappearance of carbon-to-carbon double bonds due to the successful free radical polymerization reaction. The high enthalpy of fusion for PEGDMA and irgacure 2952 (86.1409 kJ/mol) suggested that they required high energy to melt, while their exothermic crystallization enthalpy (21.35378 kJ/mol) indicated the heat release upon solidification. Adding hydroxyapatite reduced these enthalpies, indicating easier melting and solidification, which may aid processing thus opens new possibilities for biomedical applications, particularly in dentistry.